Irradiation-induced microstructure damage in He-irradiated 3C-SiC at 1000℃. Issue 4 (April 2020) - Li, Bingsheng; Liu, Huiping; Shen, Tielong; Xu, Lijun; Wang, Jie; Zhao, Fuqiang; Peng, Dingping; Li, Junhan; Sheng, Yanbin; Xiong, Anli
Abstract: The effect of the high-temperature helium irradiation on microstructural evolution of 3C-SiC was investigated by the combination of Raman spectroscopy, conventional transmission electron microscopy (TEM) and high resolution transmission electron microscopy (HRTEM). 3C-SiC wafers were irradiated with 130 keV He + ions at fluences of 2 × 10 16 He + /cm 2, 4 × 10 16 He + /cm 2 and 2 × 10 17 He + /cm 2 at 1000℃. Helium bubbles, dislocation loops, and their interaction with the stacking faults were focused on and characterized by TEM. Helium bubbles preferentially nucleate and grow on stacking faults. Bubble links on the (100) plane in 3C-SiC are formed. In addition, stacking faults can effectively trap irradiation-induced lattice defects to enhance their recovery. The type of irradiation-induced lattice defects and elemental distribution are also investigated. The research results are valuable for the 3C-SiC used in the advanced nuclear energy systems.